Tingkat Konsumsi Macaca Hecki Terhadap Jenis Tanaman Budidaya Pertanian Desa Makarti Jaya, Pohuwato Gorontalo - Frandika K. Toiyo; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to analyze the level of attack by Macaca hecki on cultivated plants in Makarti Jaya Village, Pohuwato, Gorontalo. Agriculture is the main source of income for the local community, but the presence of Macaca hecki can threaten agricultural yields. The method used in this research is descriptive qualitative, with data collected through direct observation and interviews with farmers experiencing the attacks. The results indicate that corn (Zea mays) is the most consumed plant by Macaca hecki, followed by cocoa (Theobroma cacao) and several other types of fruit such as bananas and papayas. The high consumption rates of these cultivated plants negatively impact agricultural results, causing significant economic losses for farmers. Therefore, it is important to understand the attack patterns and the factors influencing the behavior of Macaca hecki. This research recommends the need for more effective protection strategies, such as the placement of physical barriers and diversification of plant types. Thus, it is hoped that this study can contribute to the management of conflicts between wildlife and agriculture, as well as enhance the economic sustainability of farming communities.